Uma jornada de (re)educação pessoal e profissional - Sérgio Miguel Carvalho (2023)
This internship report was prepared with a view to obtaining a master's degree in teaching physical education in Basic and Secondary Education and aims to recount the experiences lived, the learning achieved, the challenges overcome, the personal and professional growth, the reflections made, as well as publicize the study carried out within the scope of inclusion in Physical Education classes. The professional internship carried out at the Pero Vaz de Caminha school, had an internship group of four elements, two boys and two girls, two cooperating teachers from the school, one responsible for the 1st and 2nd cycle, another responsible for the 3rd cycle as well as an advisor at the Faculty of Sports of the University of Porto. This document aims to recount the countless challenges and adventures that arose along this journey, as well as analyze this whole new world in which the student intern immersed himself. It is through this document that I make myself known as a person, that I report all my experience in the world of sport and throughout the academic year. Starting with the initial difficulties felt, the mix of feelings and emotions from the first class I taught to the last, the shock of reality when the class presented itself for the first time, the challenges and problems I had to overcome as well as the solutions I found For the setbacks that were imposed on me, this entire rollercoaster that is teaching is described throughout this document. A unique and genuine document that closes one of the most important stages of my life.